PENERAPAN LINE BALANCING UNTUK MENINGKATKAN EFISIENSI PRODUKSI OBAT F2 DI PT.P. - Sarinindiyanti, Julin Arum (Jurnal Inovasi Teknik Industri, 2025)
PT. P is one of the pharmaceutical companies widely known in Indonesia, producing various types of health-related products, including medicines and medical devices. One of the products manufactured by PT. P is the F2 drug. Field observations and interviews conducted during the production process of the F2 drug revealed several production issues. These issues include waiting times and bottlenecks at certain workstations. This study was conducted to analyze line balancing in the production of the F2 drug to achieve an optimal production process. The research provides alternative proposals that improve the balance of the production line compared to the initial condition.